$\displaystyle f(x)=-6*e^x*sin(x)$ The problem is: -6*e^(x*sin(x)) What are the steps for this? is 'u' u^(x*sin(x))
Follow Math Help Forum on Facebook and Google+
Originally Posted by Zanderist $\displaystyle f(x)=-6*e^x*sin(x)$ The problem is: -6*e^(x*sin(x)) What are the steps for this? is 'u' u^(x*sin(x)) Oops, sorry, I did not read the problem correctly
Last edited by ione; Mar 13th 2010 at 03:39 PM.
Originally Posted by Zanderist $\displaystyle f(x)=-6*e^{x*sin(x)}$ The problem is: -6*e^(x*sin(x)) What are the steps for this? is 'u' u^(x*sin(x)) $\displaystyle y = -6e^u$ , where $\displaystyle u = x\sin{x}$ $\displaystyle \frac{dy}{dx} = -6e^u \cdot \frac{du}{dx}$